Analysis of Servant Leadership on Employee Performance: An Empirical Study in Oil Palm Companies - Dahniar; Mohammad Adhiya Riswandha; Mohammad Yudy Rachman (PT. Berkah Digital Teknologi, 2024)
Purpose of the study — The focus of the research is to investigate and evaluate the influence of servant leadership on employee performance in South Kalimantan palm oil enterprises, incorporating organizational citizenship behaviors as the intervening variable. Research method— This study employed a proportional random sampling technique involving 78 employees in palm oil companies in South Kalimantan. To evaluate the model, Structured Equation Modelling (SEM) was applied. Result— The results reveal that servant leadership has a positive impact on employee performance and organizational citizenship behaviors. Additionally, as hypothesized, organizational citizenship behavior partially mediates the relationship between servant leadership and employee performance Conclusion— These findings provide insights and a better understanding of how servant leadership plays a significant role in affecting employee performance in the organization, especially in the palm oil companies in South Kalimantan